A model for slash-and-burn using cellular automata. (2016) - Fujioka, Kaoru; Abe, Sayaka
Slash-and-burn is one of the efficient ways to clear land for fields or increase the soil fertility of established fields, in which farmers intentionally set fires to their field. On the other hand, a cellular automaton is used to simulate fire spread such as forest fire. Therefore, in this paper, we demonstrated fire spread during slash-and-burn using a two-dimensional cellular automata. We proposed and simulated some ways of fire ignition based on principles experimentally derived in Japan using cellular automata models. Our model took in such parameters as bush density, and the probability of fire-spread. We showed that those two parameters are essential for fire-spread. By comparing various firing methods, the number of ignition points effected the time to burn out the field. These results can serve as a prediction for the actual slash-and-burn and a planning firings or creating manuals from the perspective of mathematics.